Operation process for improving adhesion of polymerization kettle

By employing electrolytic polishing, nano-coating, composite anti-sticking agents, and steam atomization technology on the polymerization reactor, the problem of reactor sticking was solved, the anti-sticking performance and cleaning efficiency were improved, the equipment life was extended, and the cost was reduced.

CN121338653APending Publication Date: 2026-01-16内蒙古三联化工股份有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511486603.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-17
Publication Date
2026-01-16

AI Technical Summary

Technical Problem

Traditional methods for solving the problem of adhesion to polymerization reactors suffer from problems such as poor durability of anti-sticking agents, inadequate cleaning effect, and short equipment lifespan.

Method used

Electrolytic polishing of the vessel wall and spraying of a nano-silica coating are employed, combined with staged spraying of composite anti-sticking agent, dynamic liquid level control, high-pressure water initial cleaning and secondary steam atomization technology at the bottom of the vessel, and intelligent vessel cleaning cycle decision-making, to form a hydrophobic surface and precisely clean dead corner areas.

Benefits of technology

It significantly improves the anti-sticking performance and cleaning efficiency of the polymerization reactor, extends the anti-sticking cycle, reduces water waste, lowers production costs, and extends equipment lifespan.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121338653A_ABST
    Figure CN121338653A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of chemical processes, in particular to an operation process for improving adhesion of a polymerization kettle, which comprises the following steps: S1, pretreating the surface of the polymerization kettle; s2, deoxidizing the system and controlling impurities; s3, spraying the composite anti-sticking kettle agent in stages; s4, dynamic liquid level control in the reaction process; s5, high-pressure water preliminary cleaning is carried out after polymerization is finished; s6, secondary atomization of steam at the bottom of the kettle; s7, making an intelligent kettle cleaning cycle decision; according to the invention, through integration of a plurality of technologies such as electrolytic polishing, nano coating, composite anti-sticking agent, dynamic liquid level control, high-pressure water preliminary cleaning, steam secondary atomization and intelligent kettle cleaning decision, the anti-sticking performance and cleaning efficiency of the polymerization kettle are obviously improved, and the composite anti-sticking agent staged spraying technology combines the durability of a base coat and the hydrophilicity of a top coat; the anti-sticking period is effectively prolonged, and the kettle bottom steam secondary atomization technology utilizes steam to activate the residual anti-sticking agent, so that the accurate cleaning of dead angle areas is realized.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of chemical engineering, in particular to an operation process for improving adhesion of a polymerization kettle. BACKGROUND

[0002] The polymerization kettle is a key reaction equipment in chemical production, which is widely used in the synthesis of high polymer materials such as plastics, rubber, fiber and paint. By precisely controlling the temperature, pressure and stirring speed, monomers can be polymerized under the action of catalyst or initiator to generate high molecular polymers. The design of the polymerization kettle needs to consider the material compatibility, heat transfer efficiency and anti-sticking kettle technology to ensure uniform reaction and stable product quality. In chemical production, the polymerization kettle not only improves the production efficiency, but also reduces the energy consumption by optimizing the reaction conditions, which is an indispensable core equipment in modern chemical industry.

[0003] In the production process of the polymerization kettle, the sticking problem has always been a key factor affecting the production efficiency, product quality and equipment life. In the traditional technology, in order to solve the sticking problem, single anti-sticking agent spraying or simple mechanical cleaning method is often used. However, these methods have many shortcomings: the single anti-sticking agent has poor durability, which needs to be frequently recoated, increasing the production cost and downtime; mechanical cleaning can easily damage the kettle wall, shortening the service life of the equipment; at the same time, the traditional method is difficult to completely remove the sticking material in the dead angle area, resulting in poor cleaning effect. SUMMARY

[0004] The purpose of the present application is to provide an operation process for improving the adhesion of a polymerization kettle to solve the problems raised in the background.

[0005] To achieve the above purpose, the present application provides the following technical scheme: an operation process for improving the adhesion of a polymerization kettle, the process method comprising the following steps: Step S1: surface pretreatment of the polymerization kettle: electrolytic polishing is used to treat the kettle wall and internal components, and nano-silica coating is sprayed to form a hydrophobic surface; Step S2: system deoxygenation and impurity control: deoxygenated pure water is injected into the polymerization kettle, vacuumed to-0.095MPa and then replaced with nitrogen; Step S3: composite anti-sticking kettle agent is sprayed in stages: the bottom coating is sprayed with an anti-sticking agent containing a polyphenol condensate using nitrogen as the carrier, the surface coating is sprayed with an atomized water-soluble polymer coating, and hot air at 60℃ is blown into the polymerization kettle for 10min; Step S4: dynamic liquid level control during the reaction process: water is injected through the DCS system to maintain the liquid level fluctuation within 5cm to prevent gas-liquid interface sticking; Step S5: high-pressure water initial cleaning at the end of polymerization: a 20MPa high-pressure water gun is used to flush the back of the baffle and the root of the stirring shaft; Step S6: secondary atomization of kettle bottom steam: open the kettle bottom valve to introduce 0.8 MPa saturated steam, last for 60 s, then open the drain valve to discharge the condensate until the conductivity is ≤10 μS / cm; Step S7: intelligent cleaning cycle decision: trigger automatic high-pressure water cleaning based on the heat transfer coefficient K value drop rate (ΔK≥15%).

[0006] Preferably, in the step S1, the electrolyte in the polishing process is a phosphoric acid-sulfuric acid mixed system, the current density is controlled to be 30 A / dm 2 , and the processing time is 20 min.

[0007] Preferably, in the step S1, the coating thickness of the nano-silicon dioxide coating is 0.5 μm, the spraying pressure is 0.4 MPa, the curing temperature is 150 ℃, the curing time is 30 min, and the contact angle of the formed hydrophobic surface is ≥110°.

[0008] Preferably, in the step S2, the vacuum is maintained for 30 min, and the nitrogen is filled and replaced 3 times during the process, and the nitrogen filling pressure is 0.3 MPa each time.

[0009] Preferably, in the step S3, the component of the anti-sticking agent containing polyphenol condensate is a dihydroxy naphthalene-formaldehyde condensate, and the ratio is 1:4, and the concentration is 5 wt%.

[0010] Preferably, in the step S3, the component of the water-soluble polymer coating is polyvinyl alcohol-polyacrylic acid colloid, and the atomized particle size of the surface coating needs to be controlled to be 10-50 μm.

[0011] Preferably, in the step S3, a hot air drying machine is used for drying, and the hot air flow is 2 m 3 / min.

[0012] Preferably, in the step S5, the flushing time is 10 min / time, and the flushing distance is 30 cm.

[0013] Preferably, in the step S6, the steam flow during the steam injection process is 100 kg / h.

[0014] Preferably, in the step S6, the kettle body needs to be preheated to 80 ℃ before steam injection.

[0015] Compared with the prior art, the beneficial effects of the present application are as follows: The application significantly improves the anti-adhesion performance and cleaning efficiency of the polymerization kettle by integrating electrolytic polishing, nano coating, composite anti-adhesion agent, dynamic liquid level control, high-pressure water initial cleaning, steam secondary atomization and intelligent cleaning decision-making and other technologies. The composite anti-adhesion agent spraying technology combines the durability of the primer and the hydrophilicity of the topcoat, effectively prolonging the anti-adhesion period. The kettle bottom steam secondary atomization technology uses steam to activate the residual anti-adhesion agent, achieving accurate cleaning of the dead angle area. The intelligent cleaning cycle decision-making system dynamically adjusts the cleaning cycle according to the actual kettle adhesion situation, avoiding water resource waste. BRIEF DESCRIPTION OF DRAWINGS

[0016] Figure 1 It is a flowchart of the process method in the application. DETAILED DESCRIPTION

[0017] The technical solutions in the embodiments of the application will be clearly and completely described below with reference to the drawings in the embodiments of the application. Obviously, the described embodiments are only part of the embodiments of the application, rather than all the embodiments of the application. Based on the embodiments in the application, all other embodiments obtained by those skilled in the art without creative labor fall within the scope of protection of the application.

[0018] An improved operation process for improving the adhesion of a polymerization kettle, the process method comprising the following steps: characterized by comprising the following steps: Step S1: surface pretreatment of the polymerization kettle: S1.1, using an electrolytic polishing machine to process the kettle wall and internal components, the electrolyte being a phosphoric acid-sulfuric acid mixed system, the current density being controlled to be 30 A / dm 2 , the treatment time being 20 min, the surface roughness after treatment being ≤0.1 μm, through electrolytic polishing and nano coating technology, the surface roughness of the kettle wall is significantly reduced to below 0.1 μm, effectively reducing polymer adhesion and prolonging the operation cycle, the phosphoric acid-sulfuric acid mixed electrolyte needs to be prepared on site according to the volume ratio of 3:1 to prevent stratification of components, and the hydrophobicity needs to be verified by a contact angle instrument after solidification; S1.2, spraying a nano silicon dioxide coating through a nano spraying device, the coating thickness being 0.5 μm, the spraying pressure being 0.4 MPa, the solidification temperature being 150°C, the solidification time being 30 min, a hydrophobic surface with a contact angle ≥110° being formed, the electrolytic polishing needs to strictly control the current density (30 A / dm 2 ) and the time (20 min) to avoid surface defects caused by over-polishing; the nano coating spraying needs to be carried out in a dust-free environment to ensure the uniformity of the coating; Step S2: System oxygen and impurity control: Use a deoxygenated pure water preparation system to prepare deoxygenated pure water, and use a vacuum pump to inject deoxygenated pure water into the polymerization kettle. The dissolved oxygen in the deoxygenated pure water is ≤2 ppm, the limit vacuum degree of the vacuum pump is -0.1 MPa, the vacuum is extracted to -0.095 MPa, and is maintained for 30 min. Nitrogen is replaced for 3 times, each time the nitrogen pressure is 0.3 MPa, and the replacement time is 10 min / time; Step S3: Composite anti-sticking kettle agent is sprayed in stages: S3.1, primer spraying: nitrogen is used as the carrier to spray the anti-sticking agent containing polyphenol condensate, the spraying amount is 0.2 g / m 2 , the nitrogen pressure is 0.5 MPa, the spraying time is 5 min, the anti-sticking agent containing polyphenol condensate is a dihydroxy naphthalene-formaldehyde condensate, and the ratio is 1:4, and the concentration is 5 wt%. The primer spraying needs to be carried out at a kettle temperature ≤40℃ to prevent the decomposition of the anti-sticking agent; S3.2, topcoat spraying: atomization spraying is used, the amount is 0.05 g / m 2 , the atomization pressure is 0.4 MPa, the spraying time is 3 min, and the component of the water-soluble polymer coating is polyvinyl alcohol-polyacrylic acid colloid. The atomization particle size of the topcoat needs to be controlled in the range of 10-50 μm to ensure the continuity of the coating; S3.3, in-situ curing: a hot air dryer is used to pass 60℃ hot air into the interior of the reaction kettle for 10 min, and the hot air flow is 2 m 3 / min; Step S4: Dynamic liquid level control during the reaction process: water is injected through the DCS system to maintain the liquid level fluctuation ≤5 cm to prevent the gas-liquid interface from sticking to the kettle. The water injection pump flow is adjusted in real time according to the liquid level feedback, and the adjustment period is 1 s. A liquid level sensor (accuracy ±1 cm) is used. Liquid level fluctuation ≤5 cm can avoid the deposition of sticking kettle materials caused by turbulent flow at the gas-liquid interface, while maintaining the reaction heat removal efficiency and preventing local overheating. The liquid level sensor needs to be installed vertically to avoid the vortex area of the stirring paddle. The water injection pump flow adjustment period (1 s) needs to be the same as the DCS scanning period. In the event of sudden liquid level fluctuation (such as interruption of feeding), the system needs to automatically switch to a safety mode (liquid level ±2 cm oscillation) to prevent dry burning of the equipment; Step S5: High-pressure water initial cleaning at the end of polymerization: a 20 MPa high-pressure water gun is used to flush the back of the baffle and the root of the stirring shaft. The flushing time is 10 min / time. The 20 MPa high-pressure water can strip more than 90% of the blocky sticking kettle materials. Especially for dead angle areas such as the back of the baffle and the root of the stirring shaft, the flushing distance needs to be kept at 30 cm to avoid close-range impact damage to the kettle wall. The rotating nozzle speed needs to be ≥300 rpm to ensure that there is no blind area. The waste water needs to be treated by three-stage sedimentation (particle content ≤50 mg / L) before being discharged to prevent blockage of the sewer; Step S6: Kettle bottom steam secondary atomization: S6.1 Steam injection: Open the bottom valve to introduce 0.8MPa saturated steam for 60s, with a steam flow rate of 100kg / h; S6.2 Anti-sticking agent activation: Steam carries residual anti-sticking agent to form micron-sized droplets that cover dead corners, such as the back side of the initiator nozzle; S6.3 Condensate Drainage: Open the drain valve to drain the condensate until the conductivity is ≤10μS / cm. The drainage time is 5-10 minutes. Activate the residual anti-sticking agent with 0.8MPa saturated steam to form micron-sized droplets (particle size 1-10μm), which deeply penetrate dead corners and reduce the amount of residue sticking to the vessel by 80%. The vessel body needs to be preheated to 80℃ before steam injection to prevent condensate accumulation. The conductivity must be ≤10μS / cm during drainage to avoid the residue of corrosive substances.

[0019] Step S7: Intelligent cleaning cycle decision: Automatic high-pressure water cleaning is triggered based on the rate of decrease of heat transfer coefficient K (ΔK≥15%). The cleaning pressure is 25MPa and the cleaning time is 30min. The heat transfer coefficient K needs to be calculated in real time through a thermocouple matrix (≥9 points) to avoid misjudgment of local scaling. The cleaning pressure (25MPa) needs to be dynamically adjusted according to the scaling thickness. The system needs to reserve a manual intervention interface to deal with sudden failures (such as sensor failure).

[0020] Table 1. Data from the Example Index Conventional process The process (70m 3 kettle) of the invention Lifting range Anti-sticking cycle 100~150 pots ≥500 pots 300% Resin fish eye number 15-20 per 100 cm 2 ]] ≤ 5 per 100 cm 2 ]] Down 70% Heat transfer coefficient K value attenuation rate Down 20% per 100 pots Down ≤8% per 100 pots Improved 60% Annual cleaning frequency 12 times ≤2 times Reduced by 83% Single-pot anti-sticking agent cost 180 yuan / pot 90 yuan / pot Down 50% A phased composite spraying method addresses the poor durability of single anti-stick agents by combining "British Blue" condensate with hydrophilic colloids, resulting in a 3-fold increase in polymerization inhibition efficiency. The amount of anti-stick agent used in the primer is only 0.2 g / m². 2 The amount of polymer coating used for the topcoat is 0.05 g / m². 2 The total consumption is reduced by 60% compared to the traditional process. The bottom steam secondary atomization: the innovative introduction of steam activation technology, using the Siping Wuhua atomization principle, increases the function of directional coverage of dead corners, reduces the amount of residue stuck to the vessel by 80%, the steam pressure is 0.8MPa, the injection time is 60s, the droplet particle size distribution is 1-10μm, breaks through the limitation of fixed vessel cleaning cycle, and reduces the vessel cleaning frequency by 50% by real-time monitoring of heat transfer coefficient. The threshold for the decrease rate of heat transfer coefficient K value is set at 15%, and the thickness of the residue stuck to the vessel is ≤0.5mm when vessel cleaning is triggered.

[0021] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.

[0022] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. An improved operating procedure for reducing polymerator adhesion, characterized by, The process method comprises the following steps: Step S1: surface pretreatment of the polymerization kettle: electrolytic polishing is used to treat the kettle wall and internal components, and nano-silica coating is sprayed to form a hydrophobic surface; Step S2: oxygen removal and impurity control of the system: deoxygenated pure water is injected into the polymerization kettle, vacuum is drawn to-0.095 MPa, and then nitrogen is replaced; Step S3: composite anti-sticking agent is sprayed in stages: the bottom coating is sprayed with an anti-sticking agent containing a polyphenol condensate using nitrogen as the carrier, the surface coating is sprayed with an atomized water-soluble polymer coating, and 60°C hot air is blown into the polymerization kettle for 10 minutes; Step S4: dynamic liquid level control during the reaction process: water is injected through the DCS system to maintain a liquid level fluctuation of ≤5 cm to prevent the gas-liquid interface from sticking to the kettle; Step S5: high-pressure water initial cleaning at the end of polymerization: a 20 MPa high-pressure water gun is used to flush the back of the baffle and the root of the stirring shaft; Step S6: kettle bottom steam secondary atomization: the kettle bottom valve is opened to introduce 0.8 MPa saturated steam, which lasts for 60 seconds, and then the drain valve is opened to discharge the condensate until the conductivity is ≤10 μS / cm; Step S7: intelligent cleaning cycle decision: automatic high-pressure water cleaning is triggered based on the decrease rate of the heat transfer coefficient K value (ΔK≥15%).

2. An improved process for operating a polymerization reactor to reduce fouling, according to claim 1, wherein: In the step S1, the electrolyte in the polishing process is a phosphoric acid-sulfuric acid mixed system, the current density is controlled to be 30 A / dm 2 , and the processing time is 20 min.

3. An improved process for operating a polymerization reactor to reduce fouling, according to claim 1, wherein: In the step S1, the coating thickness of the nano-silica coating is 0.5 μm, the spraying pressure is 0.4 MPa, the curing temperature is 150°C, the curing time is 30 minutes, and the contact angle of the formed hydrophobic surface is ≥110°.

4. An improved process for operating a polymerization reactor to reduce fouling, according to claim 1, wherein: In the step S2, the vacuum is maintained for 30 minutes, and nitrogen is replaced 3 times during the process, with a nitrogen pressure of 0.3 MPa each time.

5. An improved process for operating a polymerization reactor to reduce fouling, according to claim 1, wherein: In the step S3, the anti-sticking agent containing a polyphenol condensate has a component of a dihydroxynaphthalene-formaldehyde condensate, and the ratio is 1:4, and the concentration is 5 wt%.

6. An improved process for operating a polymerization reactor to reduce fouling, according to claim 1, wherein: In the step S3, the component of the water-soluble polymer coating is polyvinyl alcohol-polyacrylic acid colloid, and the surface coating atomized particle size needs to be controlled within 10-50 μm.

7. An improved process for operating a polymerization reactor to reduce fouling, according to claim 1, wherein: In the step S3, drying is performed using a hot air drier, and the hot air flow rate is 2 m 3 / min.

8. An improved process for operating a polymerization reactor to reduce fouling, according to claim 1, wherein: In the step S5, the flushing time is 10 minutes per time, and the flushing distance is 30 cm.

9. An improved process for operating a polymerization reactor to reduce fouling, according to claim 1, wherein: In the step S6, the steam flow during the steam injection process is 100 kg / h.

10. An improved process for operating a polymerization reactor to reduce fouling, according to claim 1, wherein: In the step S6, the kettle body needs to be preheated to 80°C before steam injection.